The Google Mass Digitisation Project at Oxford - Milne, Ronald (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
For most of the 400 years of the Bodleian Library's existence, users have had to travel to Oxford to use its collections. In recent years, Oxford has undertaken a number of focused, 'boutique' digitisation projects. Now, as a partner in the Google Library Project, an immense range of scholarly and other 19th century out-of-copyright library materials from the Bodleian's collections will be digitised en masse and will be made freely available over the internet to anyone who has Web access. Millions of books and journals will be scanned in the course of the project and the author contends that digitisation on such a scale represents a revolution in the dissemination of information that parallels the impact of the invention of printing from moveable type in the 15th century.